Porous aluminosilicates as acid catalysts for glucose dehydration to 5-hydroxymethylfurfural - Moreno Recio, Mercedes; Moreno-Tost, Ramón; Mérida-Robles, Josefa María; Santamaría-González, José; Maireles-Torres, Pedro Jesús (My University, 2015)
In the present work, the catalytic behavior of micro- and mesoporous aluminosilicates in glucose dehydration is compared. In this sense, different commercial zeolites (Beta, Y and ZSM-5, in their protonic form) and aluminum-doped mesoporous MCM-41 silica have been characterized by using different physico-chemical techniques and the dehydration of glucose has been studied by using bi-phasic systems, where the influence of experimental variables, such as nature of co-solvent, inorganic salt addition, catalyst loading and temperature and time reaction, has been optimized. Concerning the catalytic behavior, by using a biphasic water/MIBK as reaction medium and a 30 wt.% of the 10Al-MCM catalyst with respect to the substrate weight (glucose), 87 % of glucose conversion and 36 % of HMF yield were attained at 195ºC after 150 min of reaction time. However, a very positive effect was observed by using a sodium chloride aqueous solution. The large pore dimensions of aluminium doped MCM-41 silica and H-Beta catalysts together with their high acidity, with both Brönsted and Lewis centres, have led to very active acid catalysts in the dehydration of glucose to HMF. Thus, by using a biphasic water/MIBK solution, after addition of a 20 wt% NaCl, the catalytic activity is largely improved, attaining glucose conversion values higher than 94 % and 70 % of HMF yields, in a short reaction time (30 min). Moreover, no levulinic acid nor furfural were detected.
Keywords: Catálisis heterogénea; Silicatos de aluminio; HMF; Heterogeneous catalysis; Aluminosilicate; Biorefinery; Biomass; Carbohydrate